Scoping review to evaluate the effects of peer support on the mental health of young adults. Issue 8 (4th August 2022) - Richard, Jérémie; Rebinsky, Reid; Suresh, Rahul; Kubic, Serena; Carter, Adam; Cunningham, Jasmyn E A; Ker, Amy; Williams, Kayla; Sorin, Mark
Abstract : Objectives: Young adults report disproportionality greater mental health problems compared with the rest of the population with numerous barriers preventing them from seeking help. Peer support, defined as a form of social-emotional support offered by an individual with a shared lived experience, has been reported as being effective in improving a variety of mental health outcomes in differing populations. The objective of this scoping review is to provide an overview of the literature investigating the impact of peer support on the mental health of young adults. Design: A scoping review methodology was used to identify relevant peer-reviewed articles in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines across six databases and Google/Google Scholar. Overall, 17 eligible studies met the inclusion criteria and were included in the review. Results: Overall, studies suggest that peer support is associated with improvements in mental health including greater happiness, self-esteem and effective coping, and reductions in depression, loneliness and anxiety. This effect appears to be present among university students, non-student young adults and ethnic/sexual minorities. Both individual and group peer support appear to be beneficial for mental health with positive effects also being present for those providing the support. Conclusions: Peer support appears to be a promising avenue towards improving the mental health of young adults, with lower barriers to accessing these services when compared with traditional mental health services. The importance of training peer supporters and the differential impact of peer support based on the method of delivery should be investigated in future research.